2007
DOI: 10.1111/j.1440-1681.2007.04666.x
|View full text |Cite
|
Sign up to set email alerts
|

Indices of Vascular Stiffness and Wave Reflection in Relation to Body Mass Index or Body Fat in Healthy Subjects

Abstract: 1. Obesity appears to influence vascular stiffness, an important cardiovascular risk factor. An accurate picture of arterial stiffness may be obtained when a combination of various techniques is used. 2. The purpose of the present study was to assess whether the body mass index (BMI) and body fat content obtained by bioimpedance were of equal value in estimating the influence of body fatness on various indices of vascular stiffness and wave reflection. 3. A total of 175 healthy subjects was studied. Anthropome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
41
2
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(49 citation statements)
references
References 43 publications
4
41
2
2
Order By: Relevance
“…These findings suggest that although it does not have a major impact, obesity, including abdominal obesity, is an influential factor for reduced radial arterial wave reflection in a non-hospital-based, middle-aged Japanese male population. A number of studies have shown the relationship of AI to BMI and/ or WC, [14][15][16][17][18][19][20][21][22] but the results are inconclusive. The differences in the characteristics of the study subjects and in the methodology for measuring AI among the studies may have caused these discrepancies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings suggest that although it does not have a major impact, obesity, including abdominal obesity, is an influential factor for reduced radial arterial wave reflection in a non-hospital-based, middle-aged Japanese male population. A number of studies have shown the relationship of AI to BMI and/ or WC, [14][15][16][17][18][19][20][21][22] but the results are inconclusive. The differences in the characteristics of the study subjects and in the methodology for measuring AI among the studies may have caused these discrepancies.…”
Section: Discussionmentioning
confidence: 99%
“…AI is well known to be influenced by several hemodynamic and anthropometric parameters such as blood pressure (BP), heart rate and height, 13 but the influence of obesity on AI is still controversial. [14][15][16][17][18][19][20][21][22] Moreover, to our knowledge, no reports have evaluated the association between obesity, including abdominal obesity, and AI in a nonhospital-based, apparently healthy Japanese population. Understanding this association could enable us to more accurately interpret the AI value for each individual in a variety of clinical settings.…”
Section: Introductionmentioning
confidence: 99%
“…4 Resting forearm blood flow (FBF) 5 and vasodilatory capacity 6 are decreased in overweight and obese adults. Obesity is also associated with increased augmentation index (AIx), 7 a measure of pressure wave reflection that is reduced by vasodilation of muscular arteries. 8 Chronic exercise, in particular, resistance exercise training (RET), has been suggested to improve endothelial function, [9][10][11] by increasing FBF and vasodilatory capacity, which in turn may decrease the AIx.…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, only one previous study has reported associations between measures of body size and fatness with central haemodynamics estimated by radial tonometry in apparently healthy subjects. 24 These investigators showed that both central and brachial pulse pressure significantly increased across tertiles of BMI as well as tertiles of body fat (as a proportion of total body mass) assessed by bioelectrical impedance. Although these data are in alignment with our own, no objective measures of blood biochemistry or clinical characteristics (apart from BP) were presented and the different methods to assess body size (waist circumference compared with body fat by bio-impedance) 24 make it difficult to directly compare findings.…”
Section: Central Bp and Body Sizementioning
confidence: 99%
“…24 These investigators showed that both central and brachial pulse pressure significantly increased across tertiles of BMI as well as tertiles of body fat (as a proportion of total body mass) assessed by bioelectrical impedance. Although these data are in alignment with our own, no objective measures of blood biochemistry or clinical characteristics (apart from BP) were presented and the different methods to assess body size (waist circumference compared with body fat by bio-impedance) 24 make it difficult to directly compare findings. In an indigenous Australian population with and without type 2 diabetes, Maple-Brown et al 25 noted that several indices of obesity (that is BMI, waist and body weight) were inversely associated with AIx.…”
Section: Central Bp and Body Sizementioning
confidence: 99%